Health outcomes, healthcare use and development in children born into or growing up in single-parent households: a systematic review study protocol - Pia Hardelid; Jenny Woodman; Katie Harron; Alice Armitage; Elizabeth Ingram; Irina Lut (BMJ Open)
Introduction Up to a quarter of all children globally live in single-parent households. Studies have concluded that children who grow up with continuously married parents have better health outcomes than children who grow up with single or separated parents. This is consistent for key health and development outcomes including physical health, psychological well-being and educational attainment. Possible explanations include higher poverty and time limitations of parental engagement within single-parent families, but these only represent a narrow range of mechanisms. We aim to identify and synthesise the evidence on how being born into and/or living in a single-parent household compared with living in a two-parent household as a child impacts health and development outcomes, healthcare use and factors that may be driving differences.Methods and analysis We will search PubMed, Scopus and ERIC and adapt our search terms for search engines and grey literature sites to include relevant conference abstracts and grey literature. We will restrict results to English language publications from 2000 to 2020 and screen against inclusion criteria. We will categorise main outcomes into five groups of outcomes: birth outcomes, mortality, physical health, mental health and development, and healthcare use. We will use the Newcastle-Ottawa Scale to assess the methodological quality of studies. Narrative synthesis will form the primary analysis in the review. Synthesis of effect estimates without meta-analysis will follow the Synthesis Without Meta-analysis guidelines.Ethics and dissemination All documents used are publicly accessible. We will submit results to a peer-reviewed journal and international social science conferences. We will communicate results with single-parent groups and relevant charitable organisations. This review will also be included in IL’s PhD thesis.PROSPERO registration number CRD42020197890.